2014
DOI: 10.3945/ajcn.113.075481
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive electric brain stimulation reduces food intake in humans

Abstract: Our study implies that the application of anodal direct currents to the right DLPFC represents a promising option for reducing both caloric intake and appetite in humans. This trial was registered at the German Clinical Trials Register (www.germanctr.de) as DRKS00005811.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 35 publications
5
91
0
Order By: Relevance
“…Changes in food intake have been rather inconsistent with a single session of rTMS or tDCS. In the longest study to date with tDCS (8 days), the authors found a 14% decrease in calorie consumption (Jauch-Chara et al, 2014). An important bias in some studies is the use of a sham procedure without any current flow as control, instead of sham stimulation in areas that are irrelevant to food intake for example.…”
Section: Non-invasive Neuromodulation Approaches: Recent Developmentsmentioning
confidence: 99%
“…Changes in food intake have been rather inconsistent with a single session of rTMS or tDCS. In the longest study to date with tDCS (8 days), the authors found a 14% decrease in calorie consumption (Jauch-Chara et al, 2014). An important bias in some studies is the use of a sham procedure without any current flow as control, instead of sham stimulation in areas that are irrelevant to food intake for example.…”
Section: Non-invasive Neuromodulation Approaches: Recent Developmentsmentioning
confidence: 99%
“…Direct current stimulation, which has a much lower invasiveness than electroconvulsive therapy, has also been investigated to increase food intake 72 in anorexia nervosa (but without adequate sham control) or to reduce food intake in healthy volunteers, 73 but otherwise mostly in neurological (motor) disorders.…”
Section: Placebo Responders In Non-pharmacological Trialsmentioning
confidence: 99%
“…The interpretation of such null findings is generally problematic, since effects may become significant with increasing the sample size or number of tDCS sessions. Nevertheless, as compared to previous studies on tDCS and food choices (Fregni et al, 2008; Goldman et al, 2011; Montenegro et al, 2012; Jauch-Chara et al, 2014; Kekic et al, 2014; Gluck et al, 2015; Ljubisavljevic et al, 2016), we here targeted distinct brain sites derived from recent pilot experiments that were conducted with the same food picture task and hence with the same task demands as in the present study (Kumar et al, 2016). Furthermore, our tDCS study included the largest human obese sample so far.…”
Section: Discussionmentioning
confidence: 75%
“…However, this clear dichotomy seems to describe the effects in the motor cortex, which cannot be transferred to cognitive tasks per-se (Boehringer et al, 2013; Macher et al, 2014; Taubert et al, 2016). Previous studies investigating the effect of tDCS on the DLPFC suggest that anodal stimulation in lean individuals reduces food craving (Goldman et al, 2011; Montenegro et al, 2012; Kekic et al, 2014; Ljubisavljevic et al, 2016) and caloric intake (Fregni et al, 2008; Jauch-Chara et al, 2014) immediate to tDCS. The tDCS study by Gluck et al appears to be the only study to date, probing repetitive application of tDCS to the DLPFC in an solely obese cohort, resulting in decreased daily kilocalories consumed and greater percentage of weight loss as compared to cathodal and sham (placebo) stimulation (Gluck et al, 2015).…”
Section: Introductionmentioning
confidence: 97%